Exile memories and the Dutch Revolt : the narrated diaspora, 1550-1750 - Müller, Johannes (Johannes M.), 1980- (Studies in medieval and Reformation traditions, 2016)
"The Dutch Revolt (ca. 1572-1648) led to the displacement of tens of thousands of people. In Exile Memories and the Dutch Revolt, Johannes Müller shows how migrants and their descendants in the Dutch Republic, England and Germany cultivated their Netherlandish heritage for more than 200 years. Memories of war and persecution shaped new religious and political identities that combined images of suffering and heroism and served as foundational narratives of newcomers. Exposing the underlying narrative structures of early modern exile memories, this volume shows how stories about the Dutch Revolt allowed migrants to participate in their host societies rather than producing a closed and exclusive diaspora. While narratives of religious persecution attracted non-migrants as well, exile networks were able to connect newcomers and established residents"--Provided by publisher.